2009
DOI: 10.1089/jpm.2008.0254
|View full text |Cite
|
Sign up to set email alerts
|

Doctor–Patient Communication about Advance Directives in Metastatic Breast Cancer

Abstract: The majority of patients gathered information about advance directives and had made written plans, yet few discussed these plans with their providers. Explicit discussion of advance directives and patient preferences regarding end-of-life care are lacking in this setting. Facilitation of doctor-patient communication about end-of-life care is needed in order to provide quality patient care at this difficult time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 36 publications
2
21
0
1
Order By: Relevance
“…One would think that, in this situation, scripted communication improves communication between doctor and patient about end-of life care. However, Ozanne, Partridge, Moy, Ellis, and Sepucha (2009) showed that simply recording the patient's preferences does not smooth the progress of doctor-patient communication regarding these issues. Research on doctor-patient communication demonstrates that everyday discourse (also called a "shared interview" approach)-in which physician and patient contribute equally to the conversation-is necessary to personalize the visit.…”
Section: Everyday Discourse Not Scripted Communicationmentioning
confidence: 99%
“…One would think that, in this situation, scripted communication improves communication between doctor and patient about end-of life care. However, Ozanne, Partridge, Moy, Ellis, and Sepucha (2009) showed that simply recording the patient's preferences does not smooth the progress of doctor-patient communication regarding these issues. Research on doctor-patient communication demonstrates that everyday discourse (also called a "shared interview" approach)-in which physician and patient contribute equally to the conversation-is necessary to personalize the visit.…”
Section: Everyday Discourse Not Scripted Communicationmentioning
confidence: 99%
“…However, only 14% shared this information with their oncology team, and patients were more than three times as likely to talk with family and friends than with oncology providers. 20 In our study, only 3 of 60 patients (5%) who did not utilize hospice had an advance directive discussion documented with the oncology team, and only 7% had a documented discussion of palliative care as an option prior to their death.…”
Section: Discussionmentioning
confidence: 56%
“…Other studies have shown that family relationships are mostly characterised by emotional closeness and trust, and patients found it very important to include their next of kin in end-of-life decisions [23][24][25]. In this context, AD does serve the purpose not only to lay down end-of-life preferences but also to take strain of decision-making off the relatives [26].…”
Section: Discussionmentioning
confidence: 99%